Reaction Force Compensator for High-Speed Precision Stage of Laser Direct Imaging Process - Seo, Chang Hoon; Jeon, Yong Ho; Lee, Hyung Ku; Kim, Hyo Young; Lee, Moon G. (Shock and Vibration, 2018)
Recently, laser direct imaging (LDI) process has become popular as a substitute for lithography in flexible printed circuit board (FPCB) manufacturing industry. However, repeated motion of the process equipment causes residual vibration in a transient state when the stage accelerates or decelerates. The supporting structure for the laser head is complex and heavy in order to increase the resonant frequency, because the residual vibration must be controlled below a certain level for the LDI process precision. If the vibration cannot be rejected, the controller needs longer settling time; therefore, the productivity is reduced. In this study, a reaction force compensator (RFC) for the granite of a precision stage in the equipment is proposed to minimize the detrimental vibration and steady state error. First, displacement is measured with a laser Doppler vibrometer (LDV) to identify the dynamic characteristics of a pneumatic isolator for the stage. Second, the compensator's mechanism design is proposed by using a voice coil motor and capacitive displacement sensor. Third, a hybrid control algorithm combining the RFC and PID is applied to reduce the vibration. Finally, the RFC is evaluated in terms of vibration peak and steady state error. The LDI apparatus is stabilized more rapidly, because the proposed method cancels the impulsive reaction force of linear motion module immediately.
Keywords: Capacitive displacement sensors; Dynamic characteristics; Flexible printed circuit boards; Laser direct imaging; Laser Doppler vibrometers; Manufacturing industries; Reaction force compensator; Supporting structure